Studs Terkel : a life in words - Parker, Tony. (New York : H. Holt, 1996)
Studs Terkel: A Life in Words is the story of a broadcasting and writing phenomenon and represents the remarkable result of a sequence of meetings between the two supreme masters of the tape-recorded interview, America's Studs Terkel and Britain's Tony Parker. For forty years, Studs Terkel's daily radio talk show, based in Chicago, has won him national recognition. His best-selling books, including Hard Times, Working, and his Pulitzer Prize-winner "The Good War," are classics of oral history and have brought him international fame. In this meeting of the maestros, Tony Parker recounts Terkel's life story using Terkel's own method, that of the tape-recorded interview. Through a kaleidoscope of voices - from John Kenneth Galbraith, Mike Royko, and Calvin Trillin to Terkel's office assistant, his family, friends, and the people with whom he's worked - the master interviewer gradually emerges. But the soul of the book is found in Parker's extended interviews with Terkel himself. This is the first biography with which Terkel has cooperated, and in a series of fascinating conversations we come to know not only the highlights of his life but also the personality of the man who can discover the essence of people's lives in their answers to his questions
Keywords: Terkel, Studs, -- 1912-; Broadcasters -- United States -- Biography; Authors, American -- 20th century -- Biography